Paper-based AuNPs/Bi2S3/PbS broadband photodetector with PDMS package - Wang Shenjiali; Lv Yue; Trigub M. V. Maksim Viktorovich; Yang Xiaozhan (2025, 2025)
In this work, PbS/Bi2S3 paper-based devices were fabricated by a two-step hydrothermal method, modified with gold nanoparticles (AuNPs), and finally packaged with dimethylsiloxane oil (PDMS). The obtained AuNPs/PbS/Bi2S3 flexible photodetector exhibits a broadband response under 365–1550 nm. Under 638 nm irradiation and 2.2 mW/cm2 of optical power, the responsivity (R) can reach 125.13 mA/W, the specific detectivity (D*) is 4.26×1010 Jones, and the external quantum efficiency (EQE) is 24.32 %. The photoelectric performance of the AuNPs/PbS/Bi2S3 flexible photodetector is enhanced several times compared with the original Bi2S3 flexible paper-based device. In addition, after the PDMS packaged device, the R and D* are 87.59 mA/W and 4.55×1010 Jones, respectively. The photocurrent loss of the device is only 1 % and no significant performance degradation occurs after stored in the air for one month. Combining the precious metal particles and packaging improves the optoelectronic performance of the flexible photodetector, and offers an effective method to produce high-performance flexible photovoltaic devices across a large area